2012
DOI: 10.3109/07420528.2012.656163
|View full text |Cite
|
Sign up to set email alerts
|

Young Women With Major Depression Live on Higher Homeostatic Sleep Pressure Than Healthy Controls

Abstract: There is mounting evidence for the involvement of the sleep-wake cycle and the circadian system in the pathogenesis of major depression. However, only a few studies so far focused on sleep and circadian rhythms under controlled experimental conditions. Thus, it remains unclear whether homeostatic sleep pressure or circadian rhythms, or both, are altered in depression. Here, the authors aimed at quantifying homeostatic and circadian sleep-wake regulatory mechanisms in young women suffering from major depressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 85 publications
4
26
0
Order By: Relevance
“…The literature is rather consistent in reporting associations between depressive symptoms and sleep impairment already in young age [50,51]. However, in our study only one connection between the total BDI score and sleep was found in younger women, where hypersomnia rather than sleep impairment was connected with depressive symptoms.…”
Section: Discussionsupporting
confidence: 44%
“…The literature is rather consistent in reporting associations between depressive symptoms and sleep impairment already in young age [50,51]. However, in our study only one connection between the total BDI score and sleep was found in younger women, where hypersomnia rather than sleep impairment was connected with depressive symptoms.…”
Section: Discussionsupporting
confidence: 44%
“…When evaluated in depressed and non-depressed women, frontal delta EEG was elevated in women with major depressive disorder (MDD) across the whole of the 24 h day with a peak elevation between 04:00 and 08:00h. This suggests that women with MDD exhibit an exaggerated form of hypofrontality and that this phenomenon peaks at time that overlaps with the time frame of interest (the peak in suicide that occurs from 00:00 to 05:00) [22]. These effects maybe further exaggerated by sleep inertia thus creating increased vulnerability to hypofrontality in the period extending from when the nocturnal awakening occurs to up to 25 min following such awakenings [23].…”
Section: Circadian and Homeostatic Effects On Frontal Eeg Activity Anmentioning
confidence: 99%
“…In a similar vein, this finding was later observed in MDD individuals, albeit only in men [5]. Conversely, we previously showed that young MDD women devoid of co-morbid sleep disturbances exhibit higher, not lower, frontal non-REM delta EEG activity (0.75–4.5 Hz), a classical marker of homeostatic sleep pressure, during both baseline and recovery sleep subsequent to SD, as compared to that of healthy young and older women [11,12]. Furthermore, MDD women exhibited higher frontal low-frequency (FLA) wake EEG activity (0.5–5.0 Hz) during SD than that of healthy controls, particularly during the biological night [13].…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, MDD women exhibited higher frontal low-frequency (FLA) wake EEG activity (0.5–5.0 Hz) during SD than that of healthy controls, particularly during the biological night [13]. Together, these data indicate that young, moderately depressed women without sleep disturbances do not exhibit a deficiency in the sleep homeostatic process S, as predicted by the S-deficiency hypothesis, but may rather live on an elevated level of homeostatic sleep pressure [11,12]. Thus, concurrent sleep disturbances may play a key role both in the pathophysiology of depression and in the antidepressant response to SD.…”
Section: Introductionmentioning
confidence: 99%